Analytical aspects of anti-crisis measures of public administration - T. K. Miroshnikova; I. A. Kirichenko; S. Dixit (Управление)
The study of crises is one of the most important areas of economic science. Sanctions against Russia in 2022 have led to significant functional and structural shifts in the national economy. Effective anti-crisis management in crisis conditions becomes one of the main directions of its overcoming in Russian economy. The issues of improving the mechanism of crisis management at the present historical stage are actualised. The purpose is study of anti-crisis management methods for the development of an effective anti-crisis mechanism. Objectives is to study the existing methods of anti-crisis management in the light of international experience. The authors used methods of analysis, synthesis and comparison, and abstract-logical method in the research. The analytical method of information processing, synthesis and deduction of theoretical aspects of the concept of crisis and crisis management was carried out. A study of methods of crisis management, considering international experience, systematization and analysis of existing principles of state crisis management of the economy was carried out. The content and role of modern methods of crisis management deserves special attention. In the context of the sanctions announced against Russia, it is necessary to develop more advanced approaches to crisis management. The model of the anti-crisis mechanism for building an effective management system in the country’s economy is considered.